Technoecomonic optimization and working fluid selection for an engine coolant driven turbo-compression cooling system - Young, Derek Nicholas, author; Bandhauer, Todd M., advisor; Quinn, Jason C., committee member; Burkhardt, Jesse, committee member (Colorado State University. Libraries, 2018)
The abundance of low grade waste heat presents an opportunity to recover typically unused heat energy and improve system efficiencies in a number of different applications. This work examines the technoeconomic performance of a turbo-compression cooling system designed to recover ultra-low grade (≤ 100°C) waste heat from engine coolant in large marine diesel engine-generator sets. In addition, five different working fluids (R134a, R152a, R245fa, R1234ze(E), and R600a) were studied for this application to better understand the effects of fluid properties on technical and economic system performance. A coupled thermodynamic, heat exchanger, and economic model was developed to calculate the payback period of the turbo-compression cooling system. Then, the payback period was minimized by optimizing the surface area of the heat exchangers by varying the effectiveness of the heat exchangers. The sensitivity of the payback period to the heat exchanger effectiveness values was quantified to inform future design considerations. The turbo-compression cooling system with R152a had the lowest payback period of 1.67 years and an initial investment of $181,846. The R1234ze(E) system had the highest cooling capacity of 837 kW and the highest overall COP of 0.415. The R152a system provided cooling for $0.0060 per kWh which was nearly 10 times cheaper than the cost of cooling provided by a traditional electrically driven vapor compression system onboard a marine vessel.
Keywords: plate heat exchanger; vapor compression cycle; organic Rankine cycle; waste heat recovery; technoeconomic optimization